Agricultural land degradation consequences as a migration driver in Egypt - Muhammad Hussien; Abdelrahman Ali; Yanwen Tan; Mohamed Abdelhameed (PLoS ONE, 2026)
Environmental migration is a global phenomenon in which increasing soil salinity reduces productivity and income, thereby increasing migration intention (MI) in affected regions. This study investigates how agricultural land degradation (ALD), particularly soil salinity, reduces productivity and influences MIs in Egypt. Employing Protection Motivation Theory (PMT) as a framework, we analyzed primary data from 1,782 respondents using a multinomial logistic model. The empirical findings revealed that socioeconomic characteristics, agricultural engagement, and ALD significantly shape and determine MI. Furthermore, over 35.8% of respondents reported a decline in land productivity in the past decade due to environmental change, with 22.4% actively seeking relocation. Among those willing to migrate, the capital Cairo (40.2%) and international destinations (29.4%) were the most desired. Additionally, gender, age, and income adequacy were identified as crucial predictors in migration dynamics. The findings challenge conventional demographic assumptions by revealing a significant propensity to migrate among older populations and women, groups often considered less mobile. The primary motivations (employment and income) are directly exacerbated by ecological pressures, such as declining land productivity. Therefore, effective policy must address this nexus to reduce threat appraisal by implementing sustainable land and water management and investing in both environmental adaptation (e.g., soil restoration) and human capital (e.g., education, local economic opportunities) to mitigate displacement pressures and foster sustainable rural resilience.